Catalytic combustion of methane on Co/MgO: characterisation of active cobalt sites - Ulla, Maria Alicia del H. (2001)
A series of Co/MgO catalysts with 3–12 wt.% Co were prepared by impregnation and calcined at 1073 K for 10 h. The catalytic behaviour of these samples toward CH4 combustion was found to increase with cobalt loading, though a plateau was reached at ca. 9 wt.% Co content. Bulk characterisation was carried out using XRD, TPR and Raman spectroscopy, and showed that the solids were made up of a CoO–MgO solid solution and a MgO phase. A detailed examination of their surfaces was achieved through FTIR spectroscopy of adsorbed CO probe molecules, which indicated that at low cobalt loadings only a small proportion of the Co going into the solid solution was present on exposed faces as either Co2+ oxo-species or pentacoordinated Co2+. However, as the cobalt content of the samples increased, a larger amount was exposed on the surface. This effect levelled off at 9 wt.% Co, after which the increase in exposed Co2+ sites was countered by the masking effect of islands of MgO. In addition, at high cobalt loadings (9 and 12 wt.%) Co formed small clusters which showed bulk CoO-like behaviour. Consequently, the benefit of having surface Co2+ species was balanced by the clustering effect of these species and the presence of MgO islands, negating their contribution to the overall catalytic activity of the samples.